Effect of agricultural intervention on nutrient stoichiometry from root to leaf in the helophyte species Glyceria spiculosa - Wei, Tian; Dongjie, Zhang; Guanglan, Cao; Wanling, Xu; Weihong, Zhu; Lei, Qin (Frontiers in Ecology and Evolution, 2022)
Plant nutrient stoichiometry indicates the balance of plant internal nutrients and its nutrient-use strategies in response to environmental changes. However, the responses of nutrient stoichiometry in different wetland plant organs under agricultural intervention are poorly understood. Here, we compared the nitrogen (N), phosphorus (P), and the ratio of N:P in the plant organs (leaves, stems, roots, and root hair) of a typical helophyte plant (Glyceria spiculosa) in reference, drained, nutrient-rich, and cultivated wetlands (CW) located downstream of the Tumen River in Northeast China. Compared with that in reference wetlands (RW), the results indicate that the average N content in plant leaves, stems, roots, and root hair in nutrient-rich wetlands (NW) was significantly higher by 76, 61, 56, and 39%, respectively (p < 0.05), whereas the N content of roots and root hair in drained wetlands (DW) was significantly higher by 17 and 32%, respectively (p < 0.05). It was found that plant root P increased only in nutrient-rich and DW (p < 0.05). Interestingly, the agricultural interventions significantly affected soil N and P availability, resulting in positive effects on plant leaves, stems, roots, and root hair. Nutrient stoichiometry analysis showed the highest increase in plant leaf N:P ratio in NW, followed by that in drained and CW, but its ratio in root and root hair showed no significant changes under different agricultural interventions, which suggests that G. spiculosa allocates nutrients differently in different organs under agricultural interventions. These results imply that plant nutrient stoichiometry should incorporate various plant organs for an in-depth understanding of plant strategies against environmental changes.